2019
DOI: 10.1371/journal.pntd.0007834
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for contamination with C. trachomatis in the household environment of children with active Trachoma: A cross-sectional study in Kongwa, Tanzania

Abstract: BackgroundTrachoma, a conjunctivitis caused by repeated infections with Chlamydia trachomatis, remains a significant cause of blindness worldwide. While mass treatments with azithromycin decreases disease and infection, re-emergence occurs, indicating that elimination may require other sustainable interventions. Environmental changes largely focus on facial hygiene and latrines, but further work to identify other possible transmission targets are needed. We sought to determine, in a cross-sectional survey of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Ct DNA could be recovered from all surfaces except woven mat. These results are in line with previous work demonstrating that Ct DNA could be detected on hands, faces and clothing of individuals and water cans in households where at least one household member had an ocular Ct infection detectable by PCR [6,9,30,31]. The lack of detection from woven mat in the present study may have occurred because Ct culture in 2SP solution seeped through the material and did not leave sufficient DNA on the surface to allow later recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Ct DNA could be recovered from all surfaces except woven mat. These results are in line with previous work demonstrating that Ct DNA could be detected on hands, faces and clothing of individuals and water cans in households where at least one household member had an ocular Ct infection detectable by PCR [6,9,30,31]. The lack of detection from woven mat in the present study may have occurred because Ct culture in 2SP solution seeped through the material and did not leave sufficient DNA on the surface to allow later recovery.…”
Section: Discussionsupporting
confidence: 92%
“…According to different studies conducted in Ethiopia, the prevalence of poor TPP was high, which ranges between 45.5 and 64.4% [1,17]. Shreds of evidence have shown that individuallevel factors such as the age of the mother, husband's education, basic knowledge about trachoma, mother's attitude towards trachoma, taking health education about trachoma, time taken to the water point and frequency of getting water and also community-level factors such as residence and types of water source were affected TPP [1,7,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Trachoma is the result of repeated infection with Chlamydia trachomatis (C. trachomatis), which causes conjunctivitis in young children [2], who are the main reservoirs of infection. C. trachomatis is transmitted in infected ocular and nasal discharge via direct contact, fomites, or eye-seeking flies [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies in Tanzania, caregivers expressed frustration about the futility of washing children's faces as they would soon become dirty again from interaction with a dirty environment [11,24]. A study found contamination of household environments including clothes, bedding, and furniture with C. trachomatis [5].…”
Section: Introductionmentioning
confidence: 99%